Positive mental health, fighting stigma and promoting resiliency for children and adolescents - Hodes, Matthew; Gau, Susan Shur-Fen (London, UK : Academic Press is an imprint of Elsevier, 2016)
"Positive Mental Health for Children and Adolescents: Fighting Stigma and Promoting Resiliency examines the main mechanisms involved in improving mental health in children and adolescents, including social and biological processes, as well as effective treatments. By taking into account diverse settings and cultures, the book combines academic, research, and clinical contributions and sets forth how it can be translated into effective clinical practice. In addition, the book promotes the study, treatment, care, and prevention of mental and emotional disorders and disabilities involving children, adolescents, and their families, and includes emerging knowledge on mental health problems and good practice in child and adolescent psychiatry as relayed by experts from around the world."--
Positive mental health--what is it, how is it recognized, and can it be achieved? / B. Falissard -- ICD-11--comparison with DSM-5 and implications for child & adolescent psychiatric disorders / M.E. Garralda -- Disorders of brain development : understanding childhood psychopathology / E.P. MacMaster, M. Sembo, L.M. Langevin, K. Ma and P Croarkin -- Genetic process in resilience and vulnerability and the consequence of abuse / M. Peskin and G. Zalsman -- Resilience and developmental health in autism spectrum disorder / P. Szatmari, L. Zwaigenbaum, S. Georgiades, M. Elsabbagh, C. Waddell, T. Bennett, S. Bryson, E. Duku, E. Fombonne, P. Mirenda, W. Roberts, I. Smith, T. Vaillancourt, J. Volden -- Mental health promotion for indigenous youth / L.J. Kirmayer, E. Sheiner and D. Geoffroy -- Psychological consequences of parental migration for left-behind children / Y. Zheng -- Mental health literacy for students and teachers : a "school friendly" approach / S. Kutcher, Y Wei and M. Hashish -- Transforming cultures for the mental health care of young people : the service reform imperative / P. McGorry and SA. Goldstone -- Evidence-based parenting interventions : current perspectives and clinical strategies / D.J. Hawes and J. Allen -- Psychopharmacological treatment for depression in children and adolescents : promoting recovery and resilience / M.R. Chapman, J.L. Hughes, B.D. Kennard, T.L. Mayes and G.J. Emslie -- Treatment of eating disorders in children and adolescents / J. Derenne and J. Lock -- Seclusion in the management of highly disturbed children and adolescents / M. Yurtbasi, G.A. Melvin and M.S. Gordon.
Includes bibliographical references and index.
Online resource; title from PDF title page (ScienceDirect, viewed July 11, 2016).
Print version record.
Keywords: Child mental health; Teenagers -- Mental health; Child mental health; Teenagers -- Mental health; POLITICAL SCIENCE -- Public Policy -- Social Security; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; Mental Disorders -- therapy; Child; Electronic books